Nito Alves, o herói inimigo: acusação e diferenciação em Angola pós-independência - Santander, Marcela (2024)
Based on the analysis of historical sources, I propose a study of Nito Alves' trajectory to understand the turn of his positionality in Angola – from hero of national struggle to enemy of the State. Black man, belonging to the broad layer of newly assimilated Angolans, Nito Alves joined the anti-colonial struggles of the Movimento Popular de Libertação de Angola (MPLA) in 1966, he participated in the guerrillas in the 1st Military Political Region, an area of great military complexity, which contributed to reverberating the achievements of its members, including Nito, and elevated them as heroes, while many of the MPLA leaders were in exile. He became close to Agostinho Neto, then president of the movement. After Angola's independence in 1975, Nito held the position of Minister of Internal Administration. As the new government was constituted in the light of old and new controversies, arising mainly from colonialism, the context of the Cold War and the civil war initiated against UNITA, wich were supported by the USA, the MPLA suffered with many internal disputes over different political projects of nation: on the one hand, Nito and a network of allies from poorer classes and/or Marxists, the nitistas; on the other, a wing of the MPLA represented by members of the former Angolan elite. Accused of fractionalism and expelled from the party on May 21, 1977, Nito was accused of being responsible for an alleged attempted coup d'état that broke out soon after, on May 27 of the same year. The coup was followed by a purge of divergent thoughts within the MPLA, besides of violent social repression, with silencing and censorship imposed by the State. There is an estimated number of deaths between 8 and 30 thousand, in addition to the rise of the pragmatist wing of the party as the legitimate leaders of the country. Thus, I ethnograph the production of categories in the discursive disputes of the period, especially accusations, paying particular attention to the asymmetries of power relations. I seek to understand how these statements were able to elevate Nito to the antagonistic positions of hero and enemy and I analyze how such processes were articulated by each party to construct narratives (official and counter-official) in post-independent Angola, which still reverberate today. By way of conclusion, I reflect on the making and remaking of history in Angola and the disputes over memories, silences and forgetfulness, thinking about the effects of the past on the present and pointing out that the developments of the 27th of May mark the iteration of the dispute started before 1977. I argue that in its iteration, the disputes are updated, no longer around the ideological conceptions and political disputes that marked the context in which the 27th of May took place, but the (re)construction of the memory of the victims and of the positions they currently occupy in the Angolan context.